University-community engagement towards sustainable development: the perceptions of alumni - Abdul Rahim, Adibah; Ibrahim, Haslina; Awang Abd. Rahman @ Jusoh, Amilah; Abdullah, Nur Anisah (2012)
This paper aims at reporting on perceptions of the alumni of International Islamic University Malaysia (IIUM) on the quality of various services they received from the university. Being part of the community and major stakeholder of the university, alumni play an important role in supporting university relevance to the society and its sustainability development. Therefore, they have to engage with the university in the hope that such engagement would contribute positively to sustainability of the university. With some years of experience, alumni can suggest how operations of services in the university could be better improved to create a supportive positive learning experience for future students. This paper seeks to highlight the alumni perceptions on the quality of services rendered by the university from three dimensions, namely, academic service quality, administrative service quality, and facilities service quality. By identifying some perceptions and comments from alumni, it is hoped that this paper can serve as a guide for the university to improve and increase its quality of services.